Samuel Hooper papers - Hooper, Samuel, 1808-1875.
Correspondence, financial statements, lists, ledger sheets, and receipts relating to Hooper's investments and his import business in Boston, Mass., and his service in the Massachusetts legislature and the U.S. House of Representatives (1861-1874). Family correspondents include Hooper's father, John Hooper, and brother, Robert William Hooper. Other correspondents include William Appleton, S.T. Dana, George Morey, and Lemuel Shaw.
Merchant and U.S. representative from Massachusetts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Appleton, William, -- 1786-1862 -- Correspondence; Dana, S. T. -- 1810-1877 -- Correspondence; Hooper, John, -- -1854 -- Correspondence; Hooper, Robert William, -- 1810-1885 -- Correspondence; Morey, George, -- 1789-1866 -- Correspondence; Shaw, Lemuel, -- 1781-1861 -- Correspondence; Investments; Trading companies -- Massachusetts -- Boston; Boston (Mass.) -- Commerce -- 19th century; Massachusetts -- Politics and government -- 19th century; United States -- Politics and government -- 19th century; Legislators -- Massachusetts; Merchants; Representatives, U.S. Congress -- Massachusetts